2008
DOI: 10.11646/zootaxa.1823.1.2
|View full text |Cite
|
Sign up to set email alerts
|

A taxonomic review of the trapdoor spider genus Promyrmekiaphila Schenkel (Araneae, Mygalomorphae, Cyrtaucheniidae, Euctenizinae)

Abstract: The mygalomorph spider genus Promyrmekiaphila comprises two species known from northern and central California. The type species, P. clathrata (Simon), is considered a senior synonym of P. gertschi Schenkel and P. zebra (Chamberlin & Ivie); male and female exemplar specimens are described. A new species, Promyrmekiaphila winnemem, from Shasta and Tehama Counties in northern California, is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 4 publications
0
16
1
Order By: Relevance
“…Among largely undescribed invertebrate taxa, complementary taxonomies (e.g. Harvey et al 2008;Stockman and Bond 2008) can be a nomenclatural necessity for phylogeographic studies, especially for those workers also exploring diverse but poorly studied landscapes.…”
Section: Introductionmentioning
confidence: 99%
“…Among largely undescribed invertebrate taxa, complementary taxonomies (e.g. Harvey et al 2008;Stockman and Bond 2008) can be a nomenclatural necessity for phylogeographic studies, especially for those workers also exploring diverse but poorly studied landscapes.…”
Section: Introductionmentioning
confidence: 99%
“…38; rather than being uniformly distributed across the endite face, see Stockman and Bond 2008, fig. 10) and by having two distinct posterior median spinneret spigot types (as opposed to a single type, Stockman and Bond 2008, fig. 24).…”
Section: Taxonomymentioning
confidence: 99%
“…A recent phylogenetic treatment by Bond et al (2012b) concluded that Raven’s subfamily Euctenizinae, a group that included all of the North American cyrtaucheniids, was a monophyletic taxon that is closely related to idiopids and should be elevated to the family rank. This group comprises the eastern North American genus Myrmekiaphila Atkinson, 1886 (recently revised by Bond and Platnick 2007, also see Bailey et al 2010 and Bond et al 2012a), and the southwestern genera Neoapachella , Bond & Opell 2002, Eucteniza Ausserer, 1875, Promyrmekiaphila Schenkel, 1950 (recently revised by Stockman and Bond 2008, but also see Stockman and Bond 2007), Entychides Simon, 1888, Apomastus Bond & Opell, 2002, and Aptostichus Simon, 1891. Although the basal euctenizid lineages are probably relatively old (Bond and Hedin 2006) most of the genera are depauperate with respect to morphological and species diversity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), rather than "irregular ground sheet." Promyrmekiaphila, scored by F&al as having a "brush sheet" builds a trapdoor and burrow (Stockman and Bond 2008;Bond pers. obs.…”
Section: Methodsmentioning
confidence: 99%